Chemical pedagogy and the periodic system. (15th April 2020) - Robinson, Ann E.
Abstract: It is fairly well‐known that both Dmitri Mendeleev (1834–1907) and Lothar Meyer (1830–1895) were in the process of writing textbooks when they realized that the connection between the atomic weights of elements and their properties could lead to a classification system that encompassed all of the elements. However, little has been written about the role of chemical pedagogy in the development of the periodic table, the graphical representation of the periodic law discovered by Mendeleev and Meyer. In this article I argue that the development of the graphical representation of the periodic law was driven by chemical pedagogy from its discovery. Through an exploration of a variety of pedagogical venues and tools, including textbooks and lecture halls, interactive as well as three‐dimensional periodic tables, and periodic table wallcharts, I demonstrate that within a quarter‐century of its discovery in 1869, the periodic law had been adapted and incorporated into pedagogical practice. These activities began long before the 1920s and 1930s, a period that has been described as the point at which the periodic table became largely regarded a teaching tool rather than a representation of a law of nature, and continue to this day.